2013
DOI: 10.1111/jasp.12162
|View full text |Cite
|
Sign up to set email alerts
|

Personality, interests, and career indecision: a multidimensional perspective

Abstract: Researchers have consistently linked neuroticism to career indecision; however, other personality traits have been inconsistent predictors despite sound theoretical arguments. Similarly, little research has examined a trait‐based analysis of the relationship between vocational interests and career indecision. The purpose of the current study was to evaluate the structure of career indecision and to examine the prediction of this construct as both a unidimensional and multidimensional construct. Results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
1
16
0
1
Order By: Relevance
“…The following three examples lay out this issue. Firstly, the development of career identities and -by extension -unclear aspirations are mediators of a psychological process shaped by people's personality (Burns et al 2013;Germeijs and Verschueren 2011;Guay et al 2003;Hirschi 2012;Martincin and Stead 2014;Tokar, Fischer, and Subich 1998). Second, parents of higher social class might know better than parents of lower social class which personality traits are rewarded by the school system and the labor market and foster such skills in their children (Bowles et al 2001;Farkas 2003;Shanahan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The following three examples lay out this issue. Firstly, the development of career identities and -by extension -unclear aspirations are mediators of a psychological process shaped by people's personality (Burns et al 2013;Germeijs and Verschueren 2011;Guay et al 2003;Hirschi 2012;Martincin and Stead 2014;Tokar, Fischer, and Subich 1998). Second, parents of higher social class might know better than parents of lower social class which personality traits are rewarded by the school system and the labor market and foster such skills in their children (Bowles et al 2001;Farkas 2003;Shanahan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The following three examples lay out this issue. Firstly, the development of career identitie s and -by extension -unclear aspirations are mediators of a psychological process shaped by people's personality (Burns et al 2013;Germeijs and Verschueren 2011;Guay et al 2003;Hirschi 2012;Martincin and Stead 2014;Tokar, Fischer, and Subich 1998). Second, parents of higher social class might know better than parents of lower social class which personality traits are rewarded by the school system and the labor market and foster such skills in their childre n (Bowles et al 2001;Farkas 2003;Shanahan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Feldman (2003) notes that students with many vocational interests might experience greater career indecision because it is more difficult for them to decide on a single career option. A more recent study by Burns (2013) investigated students of different vocational interest types and concluded that interests can be strong predictors of career indecision or career certainty, respectively.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For instance, one of the first instruments of its kind is the Career Decision Scale (CDS) developed by Osipow et al (1976), which was used in several studies, including recent ones (e.g. Jordaan et al, 2009;Burns et al, 2013 & Gati, 1998;Osipow, 1999).…”
Section: Theoretical Backgroundmentioning
confidence: 99%